2017
DOI: 10.1111/oik.04591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exotic invasion on the temporal stability of natural annual plant communities

Abstract: Much work in ecology has focused on understanding how changes in community diversity and composition will affect the temporal stability of communities (the degree of fluctuations in community abundance or biomass over time). While theory suggests diversity and dominant species can enhance temporal stability, empirical work has tended to focus on testing the effect of diversity, often using synthetic communities created with high species evenness. We use a complementary approach by studying the temporal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
2
25
1
Order By: Relevance
“…We were not able to fully demonstrate the significant destabilizing effect on the total biomass (nevertheless, the evidence is suggestive, 0.05 < P < 0.1), probably because of relatively low number of replications resulting in the weak test (the replications are strongly limited by the dedicated and time‐consuming biomass sorting in these species rich plots; see Appendix ). The suggested stabilizing effect of Molinia would confirm the importance of strong stable dominant for community stability (Valone and Balaban‐Feld ).…”
Section: Discussionmentioning
confidence: 55%
“…We were not able to fully demonstrate the significant destabilizing effect on the total biomass (nevertheless, the evidence is suggestive, 0.05 < P < 0.1), probably because of relatively low number of replications resulting in the weak test (the replications are strongly limited by the dedicated and time‐consuming biomass sorting in these species rich plots; see Appendix ). The suggested stabilizing effect of Molinia would confirm the importance of strong stable dominant for community stability (Valone and Balaban‐Feld ).…”
Section: Discussionmentioning
confidence: 55%
“…When temporal stability is positively associated with diversity, reductions in consumers can result in increased dominance and reduced producer richness and a reduction in temporal stability (Mortensen et al, ). In the Portal system, however, we have observed much stronger relationships between community temporal stability and the stability of the most dominant species ( E. cicutarium ) (Valone, & Balaban‐Feld, ), a pattern often found in studies of natural communities (Hillebrand, Bennett, & Cadotte, ; Sasaki & Lauenroth, ; Winfree et al, ). While the rodent consumer treatments affected E. cicutarium abundance, they did not fundamentally change the dominance structure ( λ ) of the plant communities across the treatments (Table ).…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we had shown that invasion by a dominant exotic, E. cicutarium , was associated with a decline in annual plant community abundance and richness at this site (Valone, & Balaban‐Feld, ). Here, we took advantage of experimental manipulations of the rodent community at the Portal site to examine how variation in the kinds of rodent granivores on plots affected the temporal stability of the plants they consume.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Plant communities fluctuate in their spatial stability over time with fluctuations in community abundance or biomass over time (Valone & Balaban‐Feld, ; Wang, Jiang, Liu, et al, ; Wang, Wu, Jiang, Zhou, Liu, & Lv, ). One of the major topics of research in the field of ecology is understanding how the shifts in the composition of plant communities will impact their stability because the variation in community abundance over time can subsequently disturb the level of ecosystem services (De Mazancourt et al, ; Gross et al, ; Tilman et al, ).…”
Section: Discussionmentioning
confidence: 99%